Efficacy of biofeedback therapy in peripheral facial paralysis: a systematic review - Herranz Barroso, Sara; español, español (Revista de Investigación en Logopedia, 2024)
Peripheral facial palsy (PFP) is an acute lesion at any point along the VII cranial nerve pathway, causing alterations in the facial musculature. Currently, biofeedback techniques are used for the prevention, evaluation and/or recovery of PFP. The aim of the present review was to analyze the effects of the different forms of biofeedback on the symptoms of PFP and to observe whether the incorporation of biofeedback is equally or more beneficial for the treatment of PFP. A bibliographic search was carried out in the databases PubMed, ScienceDirect and Web Of Science, using the PICO procedure and the PRISMA 2020 methodology. A total of 204 articles were found, which, after the screening process, 12 of the studies were analyzed qualitatively. Biofeedback techniques significantly improve the symptomatology of PFP, allowing greater voluntary control of the facial musculature by the patient and are equally or more beneficial both alone and combined with other forms of intervention, being a recommended resource in speech therapy, since it allows a faster and more effective recovery of PFP.